2010
DOI: 10.4021/cr108e
|View full text |Cite
|
Sign up to set email alerts
|

Role of Genetic Polymorphism of Angiotensin-Converting Enzyme, Plasminogen Activator Inhibitor-1 and Endothelial Nitric Oxide Synthase in the Prognosis of Coronary Artery Disease

Abstract: BackgroundThis study was to investigate the effects of multiple genetic polymorphisms and conventional risk factors in the prognosis of coronary artery disease (CAD).MethodsOne hundred and fifty five patients with CAD were prospectively recruited, they were subgrouped as single vessel disease (SVD) and multiple vessel disease (MVD). All patients were detected I/D polymorphism of angiotensin-converting enzyme (ACE) gene, 4G/5G polymorphism of plasminogen activator inhibitor-1 (PAI-1) gene, and G894→T mutation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Many genes related to extracellular matrix, coagulation or healing after vascular injury were also differentially regulated (Fgb, Kng1, Serpine-1). Serpine-1 encodes protein plasminogen activator inhibitor-1, which inhibits cell migration 36 and its loss-of-function variant is associated with high cardiovascular risk 37 . Additionally, several smooth muscle cell and vascular function related genes were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Many genes related to extracellular matrix, coagulation or healing after vascular injury were also differentially regulated (Fgb, Kng1, Serpine-1). Serpine-1 encodes protein plasminogen activator inhibitor-1, which inhibits cell migration 36 and its loss-of-function variant is associated with high cardiovascular risk 37 . Additionally, several smooth muscle cell and vascular function related genes were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in the hypertrophy of the muscle and caused the instability of the atherosclerosis plaque, and was subsequently followed by unstable angina or MI. In the same study [ 69 ], the prevalence of 4G/4G genotype was significantly higher in the MACE patients, and 4G/4G genotype was more frequent in multiple vessel disease than in single vessel disease.…”
Section: Discussionmentioning
confidence: 86%
“…Survival rate of carriers with ACE Del/Del genotype was reported to be significantly lower than that of Ins/Del and Ins/Ins carriers [ 68 ]. Zhang et al [ 69 ] clearly showed, in a group of 155 patients with CAD, that major adverse cardiovascular events (MACE) occurred more frequent in patients with the Del/Del genotype of the ACE gene. In fact, the increased activity of ACE by the Del allele led to the increased production of angiotensin II and enhanced the degradation of the cardiovascular protective agent bradykinin.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies linked the increased ACE concentrations with the DD genotype, CAD [ 55 ], hypertension [ 56 ], autoimmune diseases [ 57 , 58 ] and acute respiratory distress syndrome [ 59 ]. Moreover, Zhang et al [ 60 ] reported that the DD genotype was more frequent in patients with major adverse CV events among CAD patients. On the other hand, there are studies that did not find any association of ACE I/D polymorphism and serum ACE levels in septic patients [ 61 ], age-related muscular degeneration [ 62 ] and patients with venous thromboembolism [ 63 ].…”
Section: Discussionmentioning
confidence: 99%